(Table 1) Sediment chemistry and Sulphur isotope ratios of ODP Site 127-795 - Toshiyuki Masuzawa; Jitsuya Takada; Rokuji Matsushita (PANGAEA, 1992)
Sixty sediment samples collected every 10 m from Holes 795A and 795B in the northern Japan Sea were analyzed for 27 major and trace elements using instrumental neutron activation analysis, and for total organic carbon (TOC), total nitrogen, and total sulfur (TS). Sulfur isotope ratio (d34S CDT) was measured on sedimentary framboidal pyrite isolated from sediments with a high sulfur content. The changes in redox condition of the bottom water of the sea are estimated from vertical variations of redox sensitive elements (TOC, TS, Mn, Sb, U, and As) and from TOC-TS and TS-d34S CDT relationships. These data were compared to those from a piston core (KH77-3-L4 extquotesingle) collected near Site 795. The estimated changes in the redox condition are: a variation between less oxic and less euxinic in Units 5,4B, 4A, and 3 (ca. 13-15 to 6-7 Ma); oxic but less so than that of the present Japan Sea with diagenetic sulfate reduction under very high biological productivity in Unit 2 (ca. 6-7 to 2.4 Ma); and a drastic variation between oxic, similar to the present bottom water, and euxinic, similar to that during the last glacial period in the sea, in Units IB (ca. 2.4-1.2 Ma) and 1A (ca. 1.2 Ma to the present).
Supplement to: Masuzawa, T et al. (1992): Trace-element geochemistry of sediments and sulfur isotope geochemistry of framboidal pyrite from Site 795, Leg 127, Japan Sea. In: Pisciotto, KA; Ingle, JCJr.; von Breymann, MT; Barron, J; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 127/128(1), 705-717, https://doi.org/10.2973/odp.proc.sr.127128-1.179.1992